Elaboration and standardization of a confite (dirty caramel) based on panela - Campo Vera, Yesenia; Gélvez Ordoñez, Víctor Manuel; Restrepo Ochoa, José Luis (Revista Colombiana de Investigaciones Agroindustriales, 2018)
The confectionery hard candy is defined as the products obtained from a mass of crystallized sucrose and glucose evaporated at high concentration, molded and cooled to the vitreous state. This type of products is worked at high firing temperatures. The present research aims to elaborate and standardize a hard candy based on panela and addition of glucose in order to enhance the production and consumption of panela. For which, the hard-based panela sweets were made by replacing sucrose with panela in four formulations, varying the sucrose: glucose ratio (5%, 10%, 15% and 20%) to ambient conditions (17.5 ° C and 66 ° C % HR); Evaluating the rheological characteristics of (hardness), moisture content and hedonic sensory analysis. The results showed that the caramels with addition of 5% of glucose do not present significant statistical differences (p≤0.05) in the parameter of hardness compared with the commercial sample; On the contrary, samples with 10%, 15% and 20% exhibit greater hardness. Indicating that between lower glucose is obtained a caramel of better quality since it is crystallized with less difficulty compared to sucrose.